2003
DOI: 10.1254/jphs.93.489
|View full text |Cite
|
Sign up to set email alerts
|

N-Nitrosocarbofuran Induces Apoptosis in Mouse Brain Microvascular Endothelial Cells (bEnd.3)

Abstract: Abstract. In this study, we investigated whether carbofuran, a commonly used carbamate pesticide, and N-nitrosocarbofuran (NOCF), the N-nitroso metabolite of carbofuran, have cytotoxicity in mouse brain microvascular endothelial cells (bEnd.3). Results from the MTT assay in bEnd.3 cells showed that NOCF but not carbofuran caused a remarkable decrease in cell viability. The cell death induced by NOCF appeared to involve apoptosis, based on our results from annexin V staining and electron microscopy. To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
(21 reference statements)
0
13
0
2
Order By: Relevance
“…On the other hand, Yoon et al (2001) found that the N-nitroso derivative N-nitrosocarbofuran (NOCF) of CF, but not CF induced apoptosis of CHL cells and significant G (2)/M cell cycle arrest, which were demonstrated by morphological changes, DNA fragmentation, and flow cytometric analysis, suggesting that NOCF, an important metabolite of CF, leads to the induction of cell cycle arrest and apoptosis in CHL cells. Jung et al (2003) also found that NOCF, but not CF, induced apoptotic cell death in brain microvascular endothelial cells determined by Annexin-V staining and electron microscopy, at least in part, through the ERK pathway, supporting the findings by Yoon et al (2001). These findings suggested that the mechanism of CF inducing apoptosis in cortical cells (neurons; Kim et al, 2004) is different than that in CHL/microvascular endothelial cells, in which CF did not show an apoptotic effect (Jung et al, 2003;Yoon et al, 2001).…”
Section: Carbamate Pesticides Induce Apoptosismentioning
confidence: 61%
See 1 more Smart Citation
“…On the other hand, Yoon et al (2001) found that the N-nitroso derivative N-nitrosocarbofuran (NOCF) of CF, but not CF induced apoptosis of CHL cells and significant G (2)/M cell cycle arrest, which were demonstrated by morphological changes, DNA fragmentation, and flow cytometric analysis, suggesting that NOCF, an important metabolite of CF, leads to the induction of cell cycle arrest and apoptosis in CHL cells. Jung et al (2003) also found that NOCF, but not CF, induced apoptotic cell death in brain microvascular endothelial cells determined by Annexin-V staining and electron microscopy, at least in part, through the ERK pathway, supporting the findings by Yoon et al (2001). These findings suggested that the mechanism of CF inducing apoptosis in cortical cells (neurons; Kim et al, 2004) is different than that in CHL/microvascular endothelial cells, in which CF did not show an apoptotic effect (Jung et al, 2003;Yoon et al, 2001).…”
Section: Carbamate Pesticides Induce Apoptosismentioning
confidence: 61%
“…Jung et al (2003) also found that NOCF, but not CF, induced apoptotic cell death in brain microvascular endothelial cells determined by Annexin-V staining and electron microscopy, at least in part, through the ERK pathway, supporting the findings by Yoon et al (2001). These findings suggested that the mechanism of CF inducing apoptosis in cortical cells (neurons; Kim et al, 2004) is different than that in CHL/microvascular endothelial cells, in which CF did not show an apoptotic effect (Jung et al, 2003;Yoon et al, 2001). Lee et al (2004) investigated the molecular mechanism of NOCFinduced apoptosis in CHL cells and found that NOCF caused dose-dependent upregulation of cytosolic factors, such as Bax and Bid, and the release of cytochrome c, which was accompanied by activation of caspase-9, caspase-8, and caspase-3 and the subsequent cleavage of poly(ADPribose) polymerase, suggesting that the mitochondrial pathway is primarily involved in NOCF-induced apoptosis.…”
Section: Carbamate Pesticides Induce Apoptosismentioning
confidence: 99%
“…Controversial results were reported for the cell viability assay in mammalian cells, e.g., Chinese hamster lung and ovary cells after the exposure (Yoon et al, 2001;Soloneski et al, 2008). Finally, whereas carbofuran-induced apoptosis has been reported in rat cortical cells (Kim et al, 2004), negative results have been also observed in mouse brain microvascular entothelial cells and Chinese lung fibroblasts (Yoon et al, 2001;Jung et al, 2003). Similar end-points for both genotoxicity and cytotoxicity were also applied in in vivo systems.…”
Section: Carbofuran Genotoxicity and Cytotoxicity Profilesmentioning
confidence: 99%
“…The release of pro-inflammatory cytokines, changes in the extracellular matrix environment, and generation of ceramide are likely to be major contributors of brain endothelial cell apoptosis following radiation therapy [82,83]. Toxic agents, including pesticides and heavy metals, are also implicated in caspase-3-dependent apoptotic death of brain endothelial cells [84,85].…”
Section: Fig 1 Anatomical and Functional Interactions Between Brain mentioning
confidence: 99%
“…Activation of p38-MAPK has also been implicated in apoptosis of brain endothelial cells. Specifically, exposure of brain endothelial cells to cadmium or to ischemia-reperfusion induces apoptosis via a p38-MAPKdependent pathway [84,101]. The involvement of ERK, JNK, and p38-MAPK in apoptosis of brain endothelial cells, however, is cell context-specific, and under different experimental settings, these kinases may mediate cellular responses in brain endothelial cells other than apoptosis.…”
Section: Signaling Pathways Involved In Regulation Of Brain Endothelimentioning
confidence: 99%